The Influence of High Performance Work Systems on Employee Resilience Moderated by Gender Differences in Employees of Pdam Way Rilau Bandar Lampung City - Muhammad Ilhan Akmal; Nova Mardiana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Covid-19 pandemic has resulted in an economic downturn, causing changes in work patterns. This has an impact on employee resilience, to improve resilience a high-performance work system is needed. In practice, PDAM Way Rilau Bandar Lampung City implements this system, but there is gender inequality in its implementation. The purpose of this study is to see if there is an effect of a high-performance work system on employee resilience and whether gender differences moderate this effect. The method in this study uses simple linear regression analysis and MRA which is processed by SPSS software version 23. The results of this study support the proposed hypothesis that a high-performance work system has a positive and significant effect on employee resilience and gender differences strengthen the effect of a high-performance work system on employee resilience. Suggestions for PDAM Way Rilau Bandar Lampung City to further consider providing financial rewards based on individual performance. Suggestions for PDAM Way Rilau employees of Bandar Lampung City to share some things with friends, it is hoped that the burden of problems borne by oneself will become lighter, so that it can increase resilience.